Analysis of heavy metals contamination in chue snails (Faunus ater) from estuary of the southwestern coast of Aceh Province, Indonesia - Mahfud, Mahfud; Razi, Nanda Muhammad; Nasir, Muhammad; Muchlisin, Zainal Abidin (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
The southwestern coast of Aceh Province is among the areas vulnerable to heavy metal pollution originating from human activities, including mining, agriculture, and household waste. Chue snails (Faunus ater) are among the aquatic organisms that can be used as a bioindicator of water pollution. Therefore, this study aimed to evaluate the content of Lead (Pb), Cadmium (Cd) and Mercury (Hg) in F. ater snails originating from seven estuary areas in the southwestern coast area of Aceh Province. Analysis was also carried out to determine the environmental factors affecting metal accumulation and potential risks to public health. Sampling was performed in various areas, including the Jembatan Kembar River (Aceh Singkil), Trumon River (South Aceh), Kuala Lama Tuha (Southwest Aceh), Peunaga Cut Ujong River (Nagan Raya), Suak Ribe Puteh (West Aceh), Teunom River (Aceh Jaya), and Leupung River (Aceh Besar). This study used a laboratory analysis method with Atomic Absorption Spectrophotometry (AAS) instruments to measure metal concentrations in F. ater tissue. The results showed that all samples from seven areas were contaminated with Pb, Cd, and Hg at levels ranging from 0.691 - 1.575 mg/kg, 0.285 - 0.311 mg/kg, and 0.001 0.030 mg/kg, respectively. Pb and Cd content showed high heavy metal content, which exceeded the safe threshold according to the Food and Drug Administration (BPOM), Republic of Indonesia, with the greatest concentration found in the Southwest Aceh Regency. These results showed that the consumption of F. ater had the potential to endanger public health. Therefore, it is necessary to conduct outreach to the community to increase environmental awareness and food safety.Keywords:Heavy MetalBioaccumulationEstuaryBioindicatorsFaunus aterSDGs 13SDGs 14